Uma abordagem funcional entre espécies arbóreas nativas e exóticas invasoras coocorrentes na floresta Atlântica - Dreyer, Jaqueline Beatriz Brixner (2023)
Invasive species are a growing threat to natural plant communities’ conservation. Many hypotheses seek to answer how non-native species may successfully invade new environments and what drives their success over resident native species. In this sense, this thesis aimed to investigate differences between native and invasive tree species that co-occur in the subtropical Atlantic Forest through a functional approach. In particular, our aim was to understand how species differ in terms of survival and competition, and reproduction and seed dispersal strategies, that are key stages in the biological invasion process. So, the thesis was structured in two chapters. In Chapter I, the aim was to characterize fruit and seed functional traits of six tree species, three native (Psidium cattleianum Sabine, Schinus terebinthifolia Raddi, and Cupania vernalis Cambess) and three invasive species (Psidium guajava L., Ligustrum lucidum W. T. Aiton, and Eriobotrya japonica (Thunb.) Lindl.), in order to understand how species differ in their reproductive and dispersal strategies. Moreover, we aimed to evaluate the functional role similarity between each group through the analysis of morphological functional traits of their fruiting interaction partners. In general, fleshy-fruited native and invasive species differed in their reproductive strategies. Furthermore, the invasive species interacted with a large number of similar frugivores, partially overlapping their functional roles with native species. Thus, the invasive species in this study can compete with natives for seed dispersers disrupting mutualistic frugivory interactions. For Chapter II, only the two congener species, the native P. cattleianum and the invasive P. guajava, were selected. The objective was to evaluate the plants ecological performance and their competitive ability for resources in a future climate change scenario. The study was conducted in a greenhouse where plants were grown in pots. Morphophysiological responses to three soil water availability conditions and two plant densities, alone or in competition, were evaluated. The species showed greater responses to water stress than for competition. In general, the invasive species showed higher physiological efficiency due to higher photosynthetic rates and biomass production even under conditions of resource-poor environments. Finally, the results of this thesis highlight that invasive species have partially different reproductive strategies and resource use allocation compared to native species, which reflect on their ability to invade ecosystems.